Strengthening its presence in Regions XI and XII a strategic plan for Manolette Bakeshop - Romo, Glory Dee A.; Soledad, Miguel D.; Durana, Annalee D. (Davao City School of Management, University of the Philippines Mindanao, 2007)
In its aim to offer alternative bakery products, Manolette Bakeshop has built its presence in Regions XI and Region XII with a total of 77 branches. It rapid and continuous expansion in these regions resulted to a very wide coverage with management spread thinly over these branches. Despite the company's delegation of some decision-making tasks to the Supervisors, the owner, Mr. Pedro L. Barrios, handles the major managerial tasks. To address this major concern, Mr. Joe Bales was hired to fill up the position of a General Manager. His key tasks are to streamline the operations of the company and to relive the owner with most of the arduous tasks. Confronted with many challenges and uncertainties in the bakery sector, the management has recognized the critical role of strategic planning in setting the direction of the company in five years, from Year 2008 to 2012. Taking this into account, the owner has opened its company to the scrutiny of the author to come up with an impartial assessment of the performance of the company relative to the external environment. Using the ABCDE Model by Matt Evans, the author, along with the inputs of the owner and the key personnel of the company, ascertained the internal and external factors that significantly affect the company and the potential strategies to address these factors. The tools that were proven to be invaluable in this exercise were the Internal-External Matrix, SWOT Matrix and the Quantitative Strategic Planning Matrix (QSPM). The Internal-External Matrix shows that the company can best be controlled by holding and maintaining its operations. All the possible strategies within this precondition were specified. Applying the QSPM, the alternative strategies which are the most suitable are singled out for implementation; namely, improving operational efficiency and focusing on product development. These two strategies are expected to strengthen Mr. Barrios' venture in the bakery business. Through the use of the Balanced Scorecard Method, the author aims to assist the management in directing the activities of the company towards a breakthrough performance.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, 2007
Confidential
Keywords: Strategic plan